Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations 6. Industrial Pension. For total disability Two-thirds of assessed weekly earnings, but not more than £3 a week and not less than would have been paid as disability benefit and dependant allowance if any. For partial disability. Pension proportionate to loss of earning power. Marriage Grant Up to £10 according to number of contributions. Maternity Grant £4 * Funeral Grant Adults £20 Age 10-20 years £15 Age 3-9 years £10 Under 3 years £6 Industrial Grant (paid to widow or dependants of worker killed at work) To be determined in accord with Regulations of the Minister of Social Security. * Funeral grant is not payable in respect of any person above age of 60 at beginning of scheme. Beveridge Report, para. 401. Chart 2. BENEFITS AND SUBSISTENCE RATES. Comparative Benefits - Man, wife and two children Pre-war and Present. Pre-war Amount Present Amount Period and Conditions. Unemployment 33/- per week 38/- per week 26 weeks (followed by assistance on means test). Industrial Disability Half earnings up to maximum of 30/- per week Half earnings up to 35/- (Plus 8/- for the two children). Subject to compounding for lump sums. 126/TG/377/1/1/153